A Novel and Robust Model of the GUPFC Controller System Based on Adaptive Fuzzy Logic- PI Controller to Enhance the Control System Performance in Following Reference Active and Reactive Power - Messaoud, Fatima Zahra; Tedjini, Hamza; Hazzab, Abdeldjebar; Abasi, Mahyar; Meslem, Youcef (International Journal of Integrated Engineering, 2021)
The optimal electrical power transmission problem in electrical energy transmission lines has led to increased attention to the use of flexible alternating current transmission systems (FACTS) and the design of double- and multi-circuit lines. Hence, recently, multi-converter FACTS devices have been utilized in the literature to control voltage and power of multi-circuit transmission lines. A generalized unified power flow controller (GUPFC) is one of such emerging FACTS devices that can manage voltage and power control crisis in multi-circuit lines. The GUPFC is the most advanced generation of FACTS, which will be able to control active and reactive power in at least two circuits and voltage in one circuit with the best quality possible and satisfy the operator’s all requests. This paper, for the first time, presents the use of an adaptive control system design based on the proportional-integral (PI) controller and fuzzy system to enhance the fast and dynamic responsiveness of the system. PI systems alone cannot control the GUPFC under different operation conditions such as when the default reference values of active and reactive power are changed, or transient faults occur, or a transmission line experience outage. Thus, the use of a fuzzy controller, as a powerful tool, is very efficient in solving the mentioned problems. To analyze the proposed algorithm’s results, a test system and a GUPFC based on a 48-pulse voltage source converter (VSC) are implemented in the MATLAB/Simulink environment. The satisfactory results obtained in the simulation section verify the correct performance of the suggested method.